1997
DOI: 10.1074/jbc.272.9.5821
|View full text |Cite
|
Sign up to set email alerts
|

Segments in the C-terminal Folding Domain of Lipoprotein Lipase Important for Binding to the Low Density Lipoprotein Receptor-related Protein and to Heparan Sulfate Proteoglycans

Abstract: Chylomicron and very low density lipoprotein (VLDL)1 remnants can be taken up via the endocytic ␣ 2 -macroglobulin receptor/LDL receptor-related protein (␣ 2 MR/LRP) either mediated by apolipoprotein E, or by lipoprotein lipase (LpL) or hepatic lipase associated with the lipoproteins (1-4). Recent results provide evidence that the uptake via ␣ 2 MR/LRP occurs in vivo, since remnant lipoproteins accumulate in mice that express reduced amounts of ␣ 2 MR/LRP and also lack functional LDL receptors (5). It has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 40 publications
3
40
0
Order By: Relevance
“…The investigators of the latter study concluded that HSPG binding at the cell surface is required for maintaining LPL stability. LPL's C-terminal domain also appears to be involved in the binding of the enzyme to receptors such as the LDL receptor related protein (LRP) [24,25], with the critical LRP-binding site having been demonstrated to be between residues 340 and 438. Positively charged amino acid residues in this region were replaced with Ala to test receptor binding, because LPL is expected to interact with the negative charges in LRP's cysteine-rich repeats [26].…”
mentioning
confidence: 99%
“…The investigators of the latter study concluded that HSPG binding at the cell surface is required for maintaining LPL stability. LPL's C-terminal domain also appears to be involved in the binding of the enzyme to receptors such as the LDL receptor related protein (LRP) [24,25], with the critical LRP-binding site having been demonstrated to be between residues 340 and 438. Positively charged amino acid residues in this region were replaced with Ala to test receptor binding, because LPL is expected to interact with the negative charges in LRP's cysteine-rich repeats [26].…”
mentioning
confidence: 99%
“…Nonetheless, it is interesting to note that a similar region in the C terminus of LPL has been implicated for its binding to the LDL receptor-related protein and Sortilin/neurotensin receptor-3 (4, 36, 37). Nielsen et al (36) have shown that amino acids 308 -384 and 404 -430 in LPL bind to the LDL receptor-related protein. This region is characterized by the presence of high density of positive charges and is probably exposed on the surface of the molecule (4).…”
Section: Discussionmentioning
confidence: 99%
“…In LPL, four clusters of basic amino acids are exposed on the opposite side of the molecule compared with the entrance to the catalytic site, and at least two, located in the N-terminal domain, seem to be important for HS binding (14,16,17). Participation of positive regions also in the C-terminal domain of LPL have been demonstrated (17)(18)(19). Heparin fragments of 8 -10 monomer units have been shown to bind to LPL and to displace the enzyme from endothelial sites, from synthetic heparin-covered surfaces and from surfaces covered by lipoprotein receptors (20 -22).…”
Section: Heparan Sulfates (Hs)mentioning
confidence: 99%
“…4D). A loss of a sulfate group shifted the elution position of an oligosaccharide considerably (15)(16)(17)(18)(19)(20) min in the applied gradient), while the loss of an uronic acid residue had much less impact on the elution behavior of the remaining fragment due to the protonated form of the carboxyl groups at the pH used. All fragments that originally contained a 2-O-sulfated uronic acid residue in the nonreducing end shifted position (indicated by "-2S" appended to the original peak identification) as compared with the deaminated sample in Fig.…”
Section: Partial Sequence Analysis Of Lpl-bound N-sulfated Fragments-mentioning
confidence: 99%